The A Comparative Study of Kindergarten Teachers' Perceptions of Augmented Reality and Multimedia Learning Media - Muhammad Nasyithul Ibad; Herman Tolle; Achmad Ridok (Journal of Education Technology, 2025)
There are still many teachers who have poor digital literacy. The lack of digital skills among teachers is a serious problem in 21st-century education. Based on this, the purpose of this study is to analyze the perceptions of kindergarten teachers towards two types of technology-based learning media, namely Augmented Reality (AR) and Multimedia, based on the previously modified TAM approach. The focus of this study lies in three primary constructs, namely, Perceived Usefulness, Perceived Ease of Use (PE), and Continuance Intention to Use (CI). This type of research is quantitative. The research design employs a within-subjects design involving 23 kindergarten teachers. The data collection method uses a questionnaire. The data collection instrument uses an instrument sheet. The data analysis technique employs statistical analysis, including both descriptive and inferential methods. The results of the study, specifically the descriptive analysis, indicate that AR media achieves a slightly higher average perception score than Multimedia in all three constructs. However, the Paired Sample t-test shows that this study obtained results indicating no significant difference in teacher perceptions of AR and Multimedia media (p > 0.05). It is concluded that kindergarten teachers hold relatively balanced views on both types of media in terms of usefulness, ease of use, and intention to continue using them. This study suggests that the success of integrating learning technology at the kindergarten level depends not only on the type of media but also on the readiness and positive perception of teachers, who are the primary facilitators of learning.